Thermal hazard estimation of HTP-65W with kinetic equations and heat transfer model - Liu, Shang-Hao; Wang, Yan-Ru; Su, Chung Hwei; Cao, Chen-Rui (Journal of thermal analysis and calorimetry, 2021)
Organic peroxides (OPs) have a long history in the industry. In particular, it mainly occupies a leading position in the polymer industry, so there are still emerging substances being put into the current market and applications. However, the well-known aspect of OPs in the past is reflected in their self-reactive and hazardous properties, which have continued to expand related research in the field of safety. However, even under the rich research foundation and new safety technologies, the thermal hazards caused by emerging OPs are still heard, which means that the application of new OPs still needs attention and solutions in safety area. It is necessary to update the hazard knowledge of emerging OPs and achieve the purpose of disaster reduction. Therefore, the new OP, HTP-65W was selected for this study, starting from kinetic analysis and combining the heat transfer mode of the external system to estimate and assess the overall hazard characteristics between the material and the heat exchange of the environment. The basic experiment is carried out under the technical conditions of the isothermal calorimetric test which conformed to real situation. Evaluating the thermal hazard mode of a substance can establish the determination of safety parameters, and it is essential to the actual operation process. If the substance can be controlled at a specific ambient temperature or the decomposition reaction can be prevented, the possible hazards can be eliminated. For example, HTP-65W has shorter TMR ad and TCL, which shows that HTP-65W has obvious reactivity hazards. In addition, evaluating the thermal hazards of HTP-65W in different containers can be used as a safety basis for the design of HTP-65W’s cooling system and on-site operations.